2010
DOI: 10.1155/2010/249482
|View full text |Cite
|
Sign up to set email alerts
|

Direct Microbicidal Activity of Cytotoxic T-Lymphocytes

Abstract: Cytotoxic T-lymphocytes (CTL) are famous for their ability to kill tumor, allogeneic and virus-infected cells. However, an emerging literature has now demonstrated that CTL also possess the ability to directly recognize and kill bacteria, parasites, and fungi. Here, we review past and recent findings demonstrating the direct microbicidal activity of both CD4+ and CD8+ CTL against various microbial pathogens. Further, this review will outline what is known regarding the mechanisms of direct killing and their un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Zinc deficiency also significantly lowered the percentages of cytotoxic T lymphocytes (CD3 + CD8 + cells) (Fig. b), which are required to exclude cells infected with viruses and bacteria . As mentioned above, local dermatitis was observed in rats on a zinc‐deficient diet (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Zinc deficiency also significantly lowered the percentages of cytotoxic T lymphocytes (CD3 + CD8 + cells) (Fig. b), which are required to exclude cells infected with viruses and bacteria . As mentioned above, local dermatitis was observed in rats on a zinc‐deficient diet (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…The killing mechanism of CTLs against intracellular pathogens involves MHC-restricted and antigen-specific recognition and binding of infected host cells [ 105 , 107 ]. In addition to these activities, recent studies in mammals have suggested that CTLs can exhibit direct antimicrobial activity and can kill different types of pathogens including bacteria, parasites, and fungi [ 108 ]. In contrast to killing of tumor and microbe-infected cells, direct killing of extracellular pathogens by CTLs is apparently an MHC-independent event since microorganisms do not express MHC.…”
Section: Function Of Fish T Cellsmentioning
confidence: 99%
“…T CD8 + cells are cytotoxic T-cells, which possess the ability to kill extracellular and intracellular pathogens, as well as tumourigenic cells, through the release of microbial products, known as granulysins ( Oykhman & Mody 2010 ). They are activated through a different mechanism when compared to T CD4 + cells.…”
Section: Immune Response Against Fungal Infectionsmentioning
confidence: 99%